2016
DOI: 10.37536/fitispos-ij.2016.3.0.110
|View full text |Cite
|
Sign up to set email alerts
|

The Professional Status of Public Service Interpreters. A Comparison with Nurses

Abstract: This paper aims to investigate the relationship between the professional status of public service interpreters and that which sociologists (Etzioni, 1969; Abbott and Meerabeau, 1998) have attributed to semi-professionals such as nurses. Drawing on the sociological theories of professionalization (Albrecht et al., 2003) and on certain hypotheses suggested by interpreting scholars (Sela-Sheffy and Shlesinger, 2011), the concept of semi-profession will be defined and discussed. Subsequently, the three sociologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
1
1
0
Order By: Relevance
“…Despite that, analysis of the modified professional status scale showed that nurses participating in this study frequently try to change negative views toward the nursing profession and they usually feel that patients and their families show respect and appreciation toward them. This result is in agreement with the study of [ 9 ] but in disagreement with some other studies which imply that the nursing profession is taking the right steps to reach a prestigious position [ 33 , 34 ].…”
Section: Resultssupporting
confidence: 79%
“…Despite that, analysis of the modified professional status scale showed that nurses participating in this study frequently try to change negative views toward the nursing profession and they usually feel that patients and their families show respect and appreciation toward them. This result is in agreement with the study of [ 9 ] but in disagreement with some other studies which imply that the nursing profession is taking the right steps to reach a prestigious position [ 33 , 34 ].…”
Section: Resultssupporting
confidence: 79%
“…That said, the discrepancy in status even between translators and conference interpreters is highlighted by Gentile's studies, which found that 56.5% of conference interpreters -the "stars" of the translation profession (Dam and Zethsen 2013) -"relate their status to that of medical doctors and university lecturers" (Gentile 2013, 75). However, public service interpreters were viewed more as a "semiprofession" with a status closer to that of nurses (Gentile 2016). Katan's earlier survey data showed that large numbers of translators and interpreters (50% of all responses) likened their status to teachers and secretaries ahead of lawyers, architects, or doctors (Katan 2009, 199).…”
Section: Perceptionsmentioning
confidence: 99%